The commissioning of the diamond storage ring - Bartolini, R; IEEE; Team, DMC (2007)
The Diamond storage ring has opened for user operation at the end January 2007. The storage ring has been successfully commissioned at 3 GeV in three months by December 2006. An intensive accelerator physics program has allowed the design emittance at 2.7 nm to be reached and the commissioning of the first eight insertion devices. We describe here the results of the measurements performed to characterize accelerator optics, to bring the insertion device in operation and a first analysis of orbit stability and collective instabilities, as well as plans for top-up operation.